ANALISIS FAKTOR-FAKTOR DETERMINASI INCOME SMOOTHING: STUDY PADA PERUSAHAAN ASING DAN NON ASING - Rustam Hanafi; Tri Hastuti (Universitas Islam Sultan Agung (UNISSULA), Faculty of Economics, Department of Accounting, 2012)
Profit is very important for the company internally and externally. So that management companies are always trying to be able to describe profit as possible as a reflection of the condition of the company. The phenomenon of earnings manipulation that show the existence of income smoothing practices are evolving, thus this study aimed to identify factors that affect income smoothing. This research was conducted by using the sample of manufacturing firms included in the IDX during the years 2006-2009. Recorded from 142 companies became members of the population, but only as many as 48 companies are used as samples. Analytical techniques used logistic regression. Discretionary accrual model shows that the financial risk and public ownership has a positive influence on the practice of income smoothing. But the results of tests performed by index eckle showed that only financial risk that has a positive effect on the income smoothing practices, while the factor of profitability, the firm value, managerial ownership, public ownership, auditor reputation and corporate status had no effect on income smoothing. The test results also show that discretionary accrual models are better explain those factors tested than eckle index model.